Wintering heifer calves that are to be fattened for the summer or early fall market. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
This is a report of the wintering phase of this test. Following this phase the different lots will either be full-fed or go to grass and be full-fed after the grazing period. The objective of the test is to develop a method of fattening heifers similar to the deferred full-feeding system for steer calves. The 1950-51 wintering test included: (1) a comparison of grain and no grain in the wintering ration of heifer calves; (2) a comparison of expeller type soybean oil meal pellets and hydraulic extracted cottonseed oil meal pellets.
Keywords: Beef; Heifer; Gain; Soybean oil meal pellets; Milo grain